Comparison of effectiveness in smoking cessation using nicotine replacement therapy and electronic cigarettes - Kopaczyńska, Adrianna; Szafrańska, Katarzyna; Niemirka, Szymon; Janiak, Aleksandra; Dominiczak, Kinga; Grądalski, Łukasz; Dębicki, Filip (Quality in Sport, 2025)
Nicotine, a potent psychoactive alkaloid found in tobacco leaves, is recognized for its high addictive potential, contributing to over 8 million deaths annually according to the World Health Organization. This article explores the complexities of nicotine addiction, highlighting its dual nature as both a learned behavior and a physical dependence. Despite approximately 70% of smokers expressing a desire to quit, achieving long-term cessation often requires multiple attempts, typically around six. Nicotine replacement therapy has been shown to enhance cessation success rates significantly, with various forms available, including skin patches, chewing gum, nasal and oral sprays, inhalers, lozenges, and tablets. Personalized dosing and combined pharmacotherapy with behavioral support are recommended for optimal outcomes. However, the rise of electronic cigarettes (e-cigarettes) as an alternative to traditional smoking has introduced new opportunities in smoking cessation efforts. While e-cigarettes are marketed as safer alternatives, their effectiveness in promoting long-term abstinence remains contentious, with studies indicating that they may aid short-term cessation but not necessarily improve long-term quitting rates. The impact of electronic cigarettes on smoking cessation also remains controversial, taking into consideration how little today’s medicine does know about the long-term side effects of using e-cigarettes. This article emphasizes the importance of a comprehensive approach to treating nicotine addiction, combining pharmacotherapy with behavioral support, and highlights the need for further research to evaluate the long-term safety and efficacy of e-cigarettes as cessation tools.